[Rock Island, Five Islands, Trinidad, B.W.I.] - (:unkn) unknown (My University, 2011)
The postcard features Rock Island which belongs to the group the "Five Islands" which are actually a group of six islands, also known as Las Cortorras located west of Port of Spain, the capital of Trinidad, in the Gulf of Paria. Rock Island, which has been used as a holiday home and a quarantine depot, is the second smallest island in the group. It measures roughly 50 metres by 30 metres and consists of mainly limestone.
Colour: Sepia; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Paria, Gulf of (Venezuela and Trinidad and Tobago); Islands--Trinidad and Tobago; 1904; Bodies of water--Trinidad and Tobago; Vacation homes--Trinidad and Tobago; Dwellings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Five Islands, The (Trinidad and Tobago)